Reciprocal Preferences in Matching Markets - Timm Opitz; Christoph Schwaiger (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Agents with reciprocal preferences prefer to be matched to a partner who also likes to collaborate with them. In this paper, we introduce and formalize reciprocal preferences, apply them to matching markets, and analyze the implications for mechanism design. Formally, the preferences of an agent can depend on the preferences of potential partners and there is incomplete information about the partners' preferences. We find that there is no stable mechanism in standard two-sided markets. Observing the final allocation of the mechanism enables agents to learn about each other's preferences, leading to instability. However, in a school choice setting with one side of the market being non-strategic, modified versions of the deferred acceptance mechanism can achieve stability. These results provide insights into non-standard preferences in matching markets, and their implications for efficient information and mechanism design.
Keywords: C78; D47; D82; D83; D91; 330; market design; matching; reciprocal preferences; non-standard preferences; gale-shapley deferred acceptance mechanism; incomplete information